Evaluasi Penilaian Berbasis Kelas dan Portofolio SD Negeri Karang Sari I Kota Tangerang - Ina Magdalena; Niken Ayu Shafira; Sifa Silvia Maulina; Rima Mardhiyani Yunita; Dieni Hikmah Ihsani (Jurnal Halaqah, 2020)
This journal discusses class-based assessment and portfolio-based assessment. The research method used is a description with a portfolio instrument, observation, and interviews. The study was conducted at SDN Karang Sari I, Tangerang City. The data source consisted of 27 portfolios made by grade IV children, consisting of 13 girls and 14 boys. Data was also obtained from a library clerk and a class teacher. In other words, the object of the study came from 27 respondents, who were expected from the classroom and portfolio to be able to improve the assessment system created by the teacher.